Electron‐Driven Self‐Assembly of Salt Nanocrystals in Liquid Helium1. Issue 49 (6th November 2014) - Daxner, Matthias; Denifl, Stephan; Scheier, Paul; Ellis, Andrew M.
Abstract The self‐assembly of salt nanocrystals from chemical reactions inside liquid helium is reported for the first time. Reaction is initiated by an electron impacting a helium nanodroplet containing sodium atoms and SF6 molecules, leading to preferential production of energetically favorable structures based on the unit cell of crystalline NaF. These favorable structures are observed as magic number ions (anomalously intense peaks) in mass spectra and are seen in both cationic and anionic channels in mass spectra, for example, (NaF)nNa+ and (NaF)nF−. In the case of anions the self‐assembly is not directly initiated by electrons: the dominant process involves resonant electron‐induced production of metastable electronically excited He− anions, which then initiate anionic chemistry by electron transfer.